Semangat Suporter Timnas Indonesia : Wujud Nasionalisme Di Arena Sepak Bola Dan Pengaruh Di Kancah Internasional - Dina Aulia (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Football in Indonesia plays an important role in building national identity and spirit. This study examines the impact of Indonesian supporters' enthusiasm on nationalism at the global level. Supporters, often called the "12th player," contribute to strengthening social solidarity and pride in the national team with support such as singing the national anthem and wearing national attributes. The method used in this study is a literature study. The results of the study show that the enthusiasm of supporters not only motivates athletes to excel, but also helps introduce Indonesian culture to the world. However, challenges such as conflicts between supporters must be resolved to maintain a positive image of Indonesia.